NUTRIENT CONCENTRATIONS IN COASTAL WATERS OF KHANH HOA PROVINCE - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2009)
Results of most studies on distribution of nutrients in Khanh Hoa coastal waters  (period  of  2000-2007)  were  collected  and considered.  The  statistics  indicated  that ranges of nutrient concentrations and molar ratios of N/P and N/Si are as follows:Van Phong - Ben Goi bay, NH3,4 : 0 - 69 µgN/l; NO 2 : 0 - 3.7 µgN/l , NO3 : 30 - 90 µgN/l; PO4 : 1.3 - 21.3 µgP/l; SiO3 :  44 - 968 µgSi/l; N/P:  5.83 - 93.0 and  N/Si: 0.15 - 2.7.Nha Phu lagoon - Binh Cang bay, NH3,4: 0 - 51 µgN/l; NO2 : 0 - 6.1 µgN/l , NO3: 53 - 182 µgN/l; PO4: 2.3 - 25.0 µgP/l; SiO3 : 134 - 3155 µgSi/l;  N/P: 8.95 - 47.89 and N/Si are always below 1. High concentrations of NO3 are observed in Nha Phu lagoon.Nha Trang bay, NH3,4: 0 - 34µgN/l; NO2: 0 - 2.1µgN/l , NO3 : 38 - 51 µgN/l; PO4: 1.0 -  20.0  µgP/l;  SiO3:  187  -  563  µgSi/l;  N/P:  5.33  -  39.47  and N/Si  are  always  below  1. However,  in  Cua  Be  waters,  nutrient  concentrations  are  very  much  higher  (maximum  of NH3,4: 432 µgN/l; NO2: 66.6 µgN/l, NO3: 508 µgN/l; PO4: 112.5 µgP/l;  N/P:  9.71 - 78.65 and N/Si: 0.07 - 2.63).Thuy Trieu lagoon - Cam Ranh bay, NH3,4: 0 - 296 µgN/l; NO2: 0 - 10.5 µgN/l, NO3 : 28 - 70µgN/l; PO4: 1.0 - 26.8 µgP/l; SiO3: 193 - 3845 µgSi/l; N/P: 5.82 - 166.7 and  N/Si are always below 1.Nutrient concentrations in waters almost were not high except for Nha Phu lagoon and Cua Be. N/Si ratios higher than 1 are observed in dry hot period at VanPhong - BenGoi and Cua Be.